Architectural Symbolism: Body and Space in Heinrich Wölfflin and Wilhelm Worringer. Issue 1 (30th June 2016) - Ionescu, Vlad
Abstract : The paper questions Jacques Rançière's conception of the modern aesthetic regime as the correlation between visuality and language by returning to two fundamental figures of modern art history, Heinrich Wölfflin and Wilhelm Worringer. First, Wölfflin's "Prolegomena" (1886) is interpreted as an attempt to conceive architectural space in terms of affectivity. Second, this conception of space is related to the Th. Vischer's and J. Volkelt's theory of symbolism. Third, the paper integrates this aesthetics in a model that conceives form as force (Goethe). Fourth, this modulation of affectivity that justifies architectural space is confronted with Wilhelm Worringer's concept of abstraction. After all, this notion responds also to a conception of art in terms of space and affectivity. Finally, the paper debates the role of Wölfflin's "Prolegomena" from the perspective of architectural design and its relation to modernity.